(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The financial statements must accurately, clearly and fairly present the financial situation and financial statements should be reliable as well. Pursuant to Board Decision No. (74) 2020, CBI obliges banks, according to the Banking Law No. (94) for the year 2004, Article (33) paragraph 2 concerning real estate owned from previous years and expropriated as a result debt settlement , to apply a real estate liquidation provision at a rate of 20% for each property expropriated and at a rate of 100% for each year of delay up to (5) years .also from the significance of the issue of real estates that become a property of banks as a result of debt settlement and the provision to be withheld to face the risks of seizing such real estates .This procedure helps to fairly present the financial statements of the banks .and as a descriptive, theoretical, analytical and analytical method, and the search for a group of the first of the most important (calculating the provision for liquidation real estate is one of the modern and topical topics that have a financial impact on financial management and fair disclosure) and free from fundamental errors in accordance with the regulations of accounting standards and the instructions of the Bank of Iraq , then the financial accounting that the research reached (the disposal of real estate within the legal accounting stipulated in Law No. 94) for the year 2004 that accounting for profits and business results.